Market Orientation Strategy In Improving Company Performance In The Logistics Industry In Jabodetabek - Syahyono, S. (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
This study uses industrial logistics companies as a unit of analysis, with a sample of 100 distribution companies in Jabodetabek. This research is a verification study with an explanatory survey. Data analysis used the Structural Equation Model (SEM) with the Partial Least Square (PLS) approach through the SmartPLS software. The research findings are that markets are oriented, and marketing performance tends to be quite high but not ideal. A strategic market orientation model of marketing performance moderated by environmental vulnerability The results of this study also indicate that market orientation has a positive effect on marketing performance. In this research model, market orientation strategy influences marketing performance.